Ear-to-ear lateralization of auditory image in stutterers and normals - PS, Chandra Bhushan (Journal of All India Institute of Speech and Hearing)
The study is comprised of 12 normals and 10 stutterers. All the Subjects of this study were right handers and they had normal hearing in both the ears. Their age ranged from 16 years to 30 years. Ear-to-ear lateralization test was administered for all the subjects using recorded CV syllables [pa, ba, ka, ga, ta and da] and Western music as follovvs